From water to plate: investigating the accumulation of microplastic of aquatic resources and their implication to human health - Briones, Ma. Angelica I.; Diaz, Leif Joeffrey M.; Doroin, Ervin James C.; Mercado, Rovhie Michael B.; Paculaba, Marc Efren F. (b)
Microplastics particles measuring less than 5 millimeters in diameter have become a powerful environmental pollutant, infiltrating aquatic ecosystems across the globe. In order to provide insight into the possible health impacts of microplastics on humans, this study thoroughly investigates their prevalence and effects in aquatic resources. Through literature review, systematic field surveys. And focused laboratory investigations, this study sheds light on the distribution and abundance of microplastics in various aquatic ecosystems. Our investigation explores the intricate processes by which microplastics enter aquatic systems in addition to mapping their distribution and abundance. It highlights the interdependence of our ecosystems by examining the biological mechanisms that allow microplastics to build up in species like mussels (Perna viridis) and tilapia (Oreochromis niloticus). Our research reveals concerning amounts of microplastic contamination in aquatic environments, with various ecological compartments exhibiting varied accumulation patterns. The disturbing finding that microplastics are present in a broad range of aquatic animals points to a concerning trend of ingestion and possible bioaccumulation. Research indicates that ingestion of microplastics can lead to a host of serious health complications, including cardiovascular disease, impaired kidney and liver function, metabolic disorders, neurological impacts, and reproductive and developmental issues. Each of these health threats emphasizes the urgency of understanding microplastics{92} effects not only on marine life but also on human populations that depend on aquatic resources for food. In our pursuit of a comprehensive understanding of microplastics, we employed Fourier-transform infrared (FTIR) spectroscopy, a leading technique for detecting and quantifying these pollutants. Advancements in micro-FTIR imaging technology have revolutionized our ability to detect microplastics concentrated on filter membranes without the need for prior sorting (Chen et al., 2020). A solid grasp of the spectral mechanisms underlying FTIR spectroscopy is vital for accurate characterization and quantification of microplastics within environmental samples. Our data analysis reveals striking finding that the intestines of Oreochromis niloticus and Perna viridis sourced from Laguna de Bay exhibit high-density levels of Polyethylene Terephthalate (PET). The infrared spectrum of the samples matches that of chlorinated polyethylene, confirming the identity and provenance of this harmful microplastic. This pivotal insight reinforces the need for further investigation into the specific functional groups and chemical connections associated with these prevalent polymer materials.
Undergraduate thesis.
Keywords: Oreochromis niloticus; Perna viridis; FTIR; Polyethylene; Laguna de Bay